Multisource energy conversion in plants with soft epicuticular coatings. Issue 6 (13th May 2022) - Meder, Fabian; Mondini, Alessio; Visentin, Francesco; Zini, Giorgio; Crepaldi, Marco; Mazzolai, Barbara
Abstract : Turning common plants into devices harvesting electricity from wind and radio frequency radiation endows a surprising prospect for energy-autonomous sensors. Abstract : Living plants have recently been exploited for unusual tasks such as energy conversion and environmental sensing. Yet, using plants as small-scale autonomous energy sources is often impeded by multicable and -electrode installations on the plants. Moreover, insufficient power outputs for steadily driving even low-power electronics made a realization challenging. Here, we show that plants, by a modification of the leaf epicuticular region can be transformed into cable-free, fully plant-enabled integrated devices for multisource energy conversion. In detail, leaf contact electrification caused by wind-induced inter-leaf tangency is magnified by a transparent elastomeric coating on one of two interacting leaves. This enables converting wind energy into harvestable electricity. Further, the same plant is used as an unmatched Marconi-antenna for multi-band radio frequency (RF) energy conversion. This enables the use of the same plant as a complementary multi-energy system with augmented power output if both sources are used simultaneously. In combination, we observed over 1000% enhanced energy accumulation respective to single source harvesting in the specific application case and common plants like ivy could power a commercial sensing platform wirelessly transmitting environmental data. This shows that living plants have potential to autonomously supply application-oriented electronics while maintaining the positive environmental impact by their intrinsic sustainability and benefits such as O2 production, CO2 fixation, self-repair, and many more.